1992
DOI: 10.1056/nejm199203123261102
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Human Immunodeficiency Virus Type 1 from a Seronegative Organ and Tissue Donor

Abstract: Although rare, transmission of HIV-1 by seronegative organ and tissue donors can occur. Improvements in the methods used to screen donors for HIV-1, advances in techniques of virus inactivation, prompt reporting of HIV infection in recipients, and accurate accounting of distributed allografts would help to reduce further this already exceedingly low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
256
0
23

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(279 citation statements)
references
References 23 publications
0
256
0
23
Order By: Relevance
“…Articles reviewing disease transmission by allografts have generally ignored or minimized the possibility of viral disease transmission by musculoskeletal allografts even after HIV-1 was reported in 1988 [2] and again in 1992 [33]. However, there were two reports of non-disinfected cartilage specimens from an infected donor that later showed HIV-1 in the tissues [8] and hepatitis C was reported to have been transmitted by non-disinfected bone, ligament and tendon [l 11.…”
Section: Discussionmentioning
confidence: 99%
“…Articles reviewing disease transmission by allografts have generally ignored or minimized the possibility of viral disease transmission by musculoskeletal allografts even after HIV-1 was reported in 1988 [2] and again in 1992 [33]. However, there were two reports of non-disinfected cartilage specimens from an infected donor that later showed HIV-1 in the tissues [8] and hepatitis C was reported to have been transmitted by non-disinfected bone, ligament and tendon [l 11.…”
Section: Discussionmentioning
confidence: 99%
“…27 Such measure should avoid transmission of virus from a falsely seronegative donor. 28 Tissue processing is another option that may include tissue cleaning, removal of blood and bone marrow by high-pressure washes, immersing in various solvents and thorough rinsing. Most often, processing will be completed by a secondary sterilization by irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…7,28,29 By eliminating bone marrow and blood, there is no more risk for Rhesus sensitization as described with frozen, nonprocessed bone. 30,31 In removing bone marrow from the cancellous bone of the femoral neck, the risk to transplant occult pathological conditions is further decreased.…”
Section: Discussionmentioning
confidence: 99%
“…As proposed by Simonds et al (1992), approaches to prevention could include: the screening of prospective donors and laboratory markers for HIV1 infection (MMWR, 1985); the inactivation of HIV-1 in allograft through processing techniques (Hilfenhaus et al, 1990;Kitchen et al, 1989;Wells et al, 1986) and the quarantining of tissues from living donors until repeated antibody testing more definitely excludes the possibility of subsequent seroconversion in the donor (MMWR, 1988a ;MMWR, 1988b). The U.S. Centers for Disease Control and Prevention (2002) reported that in the health care industry there have been 57 confirmed cases and an additional 139 possible cases of health care workers in the U.S. who have become HIV positive from exposure to HIV in the work place.…”
Section: Organs Blood Tissue Donors and Occupational Health Workersmentioning
confidence: 99%